2015
DOI: 10.1259/bjr.20150034
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of diffusion-weighted imaging techniques for the purposes of radiotherapy planning in the prostate

Abstract: This work will be of interest to the increasing number of centres wanting to incorporate quantitative DWI in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…Although rsEPI may reduce susceptibility‐induced distortions in DW MRI of the prostate compared with ssEPI, in this study the artifacts observed with ssEPI were mostly retained with rsEPI. Additionally, ADC values obtained by DW rsEPI largely deviated from those measured with either STEAM or ssEPI.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Although rsEPI may reduce susceptibility‐induced distortions in DW MRI of the prostate compared with ssEPI, in this study the artifacts observed with ssEPI were mostly retained with rsEPI. Additionally, ADC values obtained by DW rsEPI largely deviated from those measured with either STEAM or ssEPI.…”
Section: Discussionmentioning
confidence: 67%
“…Second, although limited to two patients, the present observations suggest that DW STEAM images and ADC maps may lead to a more accurate anatomical delineation of prostate lesions than possible with EPI. Apart from the actual diagnostic value, this property also renders DW STEAM MRI a promising choice for radiotherapy planning in the prostate . Third, DW STEAM MRI may enhance diagnostic reliability by eliminating the risk of misinterpretations of susceptibility‐induced signal alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The readout-segmented technique with navigated phase correction for DWI has been shown to reduce distortion in other tumour sites. [9][10][11] We have previously shown that this implementation of DWI results in similar geometrically shaped anatomical imaging in the prostate, 12 making it more feasible to correlate with other imaging sequences and/or modalities. However, it has not been evaluated in HNC.…”
Section: Introductionmentioning
confidence: 94%
“…Low ADC values are associated with a poor prognosis [50]. The potential of DWI for integration in target volume definition is furthermore reflected by the fact that it is already in clinical use in radiotherapy of prostate [51,52] or rectal cancer [53], among others [45]. Although a biopsy controlled study in glioma showed that ADC mapping may insufficiently distinguish tumour from peritumoral tissue [54], a recent report introduced the low ADC subvolume, that is not fully covered by the 95 % isodose of prescribed radiation dose, as a significant negative predictor for PFS [55].…”
Section: Advances In Mr Imaging For Radiation Oncology Treatment Planmentioning
confidence: 99%